Shell and Tube Heat Exchanger Fouling Factor via Heat Transfer Research Inc (HTRI) Software - Ismi Ari Fitria; Dessy Agustina Sari; Vera Pangni Fahriani; Mohammad Djaeni (Universitas Tribhuwana Tunggadewi Malang, 2022)
One of the factories for manufacturing Carboxymethyl Cellulose (CMC) uses a shell and tube-type heat exchanger as a condenser. The shell and tube (HE) heat exchanger consists of small diameter tubes arranged in a cylindrical shell. In the tube and shell sections, hot (ethanol) and cold (water) fluids will flow so that heat transfer occurs directly. The use of heat exchangers regularly will reduce the performance of the tool. Due to the increasing fouling layer inside the HE, the device will work harder, and the heat process could be more optimal. It is necessary to analyze the performance of the heat exchanger using the parameter value of the fouling factor (Rd). The fouling factor can be calculated using the manual calculation method (via the Kern method) and the HTRI program. The involvement of the mathematical equation in the first method will be configured for the calculation results through process simulation in the HTRI software. Both ways are used for calibration between manual calculations and the HTRI software for the Rd values obtained. The fouling factor can be calculated using the manual method and HTRI software. The two methods used for calibration are manual calculations with HTRI software. The results from this analysis give a decrease in tool performance with a fouling factor of 0,01 Btu/(h.ft2.℉). ABSTRAKSalah satu pabrik pembuatan Carboxymethyl Cellulose (CMC) menggunakan heat exchanger tipe shell and tube sebagai kondensor. Heat exchanger (HE) shell and tube terdiri dari sekumpulan tube berdiameter kecil yang disusun di dalam shell berbentuk silindris. Pada bagian tube dan shell akan dialirkan fluida panas (etanol) dan dingin (air) agar terjadi proses perpindahan panas secara tidak langsung. Penggunaan heat exchanger secara berkala akan mengurangi kinerja alat. Hal tersebut disebabkan oleh adanya lapisan fouling yang terus meningkat di bagian dalam HE sehingga alat akan bekerja lebih berat dan proses perpindahan panas tidak maksimal. Untuk mengatasi fenomena tersebut maka perlu dilakukan analisis kinerja heat exchanger menggunakan parameter nilai fouling factor (Rd). Fouling factor dapat dihitung menggunakan metode perhitungan manual (melalui metode Kern) dan penggunaan program HTRI. Keterlibatan persamaan matematis pada metode pertama akan dikonfigurasi hasil perhitungannya melalui simulasi proses pada software HTRI Kedua metode digunakan untuk kalibrasi antara perhitungan manual dengan software HTRI atas nilai Rd yang didapatkan. Hasil analisis perhitungan dengan kedua metode tersebut menghasilkan penurunan kinerja alat dengan nilai fouling factor sebesar 0,011 Btu/(jam.ft2.℉).